Pericapsular hip desensitization in dogs: a cadaveric study and case series. (November 2022) - Otero, Pablo E.; Portela, Diego A.; Fuensalida, Santiago E.; Romano, Marta; Tarragona, Lisa; Cavalcanti, Mariana; Texeira, Jorge G.; Jones, Rachel; Guerrero, Jorge A.
Abstract: Objective: To develop and assess the efficacy of an ultrasound (US)-guided pericapsular hip desensitization (PHD) technique in dogs. Study design: Prospective, randomized, anatomical study and a case series. Animals: A total of 30 healthy dogs, eight canine cadavers and seven dogs with hip osteoarthritis. Methods: After studying the US anatomy of the medial aspect of the coxofemoral joint and determining an acoustic window to perform an US-guided PHD in healthy dogs, the US-guided PHD was performed bilaterally in canine cadavers. A low [(LV) 0.1 mL kg –1 ] and high [(HV) 0.2 mL kg –1 ] volume of dye was injected per hip on each cadaver. The staining of the pericapsular nerves was assessed by anatomical dissection, and comparison between LV and HV was assessed using Fisher's exact test. Then, the US-guided PHD was performed using a triamcinolone–bupivacaine solution in dogs with hip osteoarthritis. Dynamic pain response was assessed before and after injection. The canine brief pain inventory (CBPI) questionnaire was used to assess treatment efficacy and duration. Results: The US-guided PHD could be performed by inserting the needle between the iliopsoas muscle and the periosteum of the ilium. The articular branches of the femoral and obturator nerves were stained in all cadavers using both volumes. The main femoral nerve was never stained, but the main obturator nerve was stained in 37.5% and 100% of injections using LV and HV, respectively ( p  = 0.026). Treated animals showed decreased dynamic pain response after the injection. Compared with baseline, CBPI scores were reduced by ≥ 50% for ≥ 12 weeks in all but one dog. Conclusions and clinical significance: The US-guided PHD with both 0.1 and 0.2 mL kg –1 volumes stained the articular branches of the femoral and obturator nerves in canine cadavers and was associated with clinical improvement in dogs with hip osteoarthritis.